Speech Recognition Implementation Using MFCC and DTW Algorithm for Home Automation - Abdulloh Salahul Haq; Muhammad Nasrun; Casi Setianingsih; Muhammad Ary Murti (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
The use of speech recognition as part of home automation, especially for smart homes, is an exciting thing that is still being developed. That is because of human needs for comfort, convenience, quality of life, and better safety. Speech recognition built in this study is used as a device to control smart home devices by identifying the commands spoken by users, especially in a state of clean speech. The command used is a predetermined consecutive word. For the extraction of voice commands, the MFCC algorithm is used to match spoken words with templates using the Dynamic Time Warping (DTW) algorithm. DTW algorithm can find the difference between 2-time series that have different lengths of time. The results of the accuracy of this system by using these algorithms were successfully carried out by 86.67%, with an average time required to identify the commands of 5.28 seconds.